Association between Gender and Utilization of Cataract Surgical Services: A Systematic Review and Meta-Analysis - Farisa Shauma Fachir; Syamsul Arifin; Silvia Kristanti Tri Febriana; Adi Nugroho; Iwan Aflanie; Tenri Ashari Wanahari (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2023)
Introduction: Cataract is the most prevalent cause of blindness worldwide, which can be effectively treated with surgery. The high incidence of blindness in women highlights the need to address gender inequality in the utilization of cataract surgery. This study aimed to assess the association between gender and the utilization of cataract surgical services. Methods: A systematic review and meta-analysis were conducted according to preferred reporting items for systematic review and meta-analysis (PRISMA) guidelines. A literature search was performed on PubMed and ProQuest in the last 10 years (2012 to 2022). The search strategy used the following terms: (